Antimelanoma differentiation‐associated protein 5 antibody level is a novel tool for monitoring disease activity in rapidly progressive interstitial lung disease with dermatomyositis. (1st February 2017) - Matsushita, T.; Mizumaki, K.; Kano, M.; Yagi, N.; Tennichi, M.; Takeuchi, A.; Okamoto, Y.; Hamaguchi, Y.; Murakami, A.; Hasegawa, M.; Kuwana, M.; Fujimoto, M.; et al.
Summary: Background: Antimelanoma differentiation‐associated protein (anti‐MDA)5 antibodies are associated with rapidly progressive interstitial lung disease (RP‐ILD) in patients with clinically amyopathic dermatomyositis (CADM) or dermatomyositis (DM). Objectives: We aimed to evaluate the relevance of monitoring anti‐MDA5 antibody levels for the management of RP‐ILD in patients with CADM or DM. Methods: Twelve patients with CADM ( n = 10) or DM ( n = 2) accompanied by RP‐ILD were included. Baseline characteristics and outcomes were recorded. Serial measurements of anti‐MDA5 antibody levels were measured. All patients were treated with corticosteroids, tacrolimus and intravenous cyclophosphamide. Results: All patients achieved RP‐ILD remission after combined immunosuppressive therapy for a mean of 6·8 months, with significant decreases noted in the mean anti‐MDA5 antibody levels at remission. Six (50%) patients became anti‐MDA5 antibody negative after therapy. After a mean follow‐up of 31 months, RP‐ILD relapse was observed in four (33%) patients in both the anti‐MDA5 antibody sustained positive group and the negative conversion group. However, relapsed patients in the sustained positive group relapsed earlier than those in the negative conversion group. Thus, a decrease in anti‐MDA5 antibody levels during remission was associated with longer remission. Relapses were associated with a reincrease of anti‐MDA5 antibody levels in four of four (100%) patients. In contrast, none of the patients without reincrease in anti‐MDA5 antibody exhibited symptoms of relapse during follow‐up. Therefore, reincrease in anti‐MDA5 antibody levels was associated with relapse. Conclusions: The anti‐MDA5 antibody level is a novel parameter for monitoring and a good predictor of RP‐ILD relapse in patients with CADM or DM.